Controls on accumulation of anomalously thick coals: Implications for sequence stratigraphic analysis. Issue 2 (6th November 2019) - Wang, Shuai; Shao, Longyi; Wang, Dongdong; Hilton, Jason; Guo, Biao; Lu, Jing
Abstract: Coal seams preserve high‐resolution records of ancient terrestrial water table (base level) fluctuations in ancient peat accumulations, but little is known about base level change in anomalously thick coal seams. Using the Early Cretaceous 91 m anomalously thick No. 6 coal (lignite) seam in the Erlian Basin (north‐east China) as a case study, the origin and evolution of peat accumulation in a continental faulted basin is revealed by sedimentological, sequence stratigraphic and coal petrological analyses. The lignite is dominated by huminite, indicating oxygen‐deficient and waterlogged conditions in the precursor mire. Four types of key sequence stratigraphic surfaces are recognized, including paludification, terrestrialization, accommodation‐reversal and give‐up transgressive surfaces. Vertically, the No. 6 coal seam consists of fourteen superimposed wetting‐up and drying‐up cycles separated by key sequence stratigraphic surfaces, with each of these cycles having a mean duration of about 156 to 173 kyr. In a high accommodation peat swamp system, the wetting‐up cycles are generally characterized by an upward increase in mineral matter and inertodetrinite and an upward decrease in huminite with the paludification surface as their base and the give‐up transgressive surface or accommodation‐reversal surface as their top, representing a trend of upward‐increasing accommodation. In contrast, the drying‐up cycles are generally characterized by an upward decrease in mineral matter and inertodetrinite and an upward increase in huminite, with the terrestrialization surface as their base and the accommodation‐reversal surface as their top, representing a trend of upward‐decreasing accommodation. A multi‐phase mire stacking model for accumulation of the coal seam is proposed based on high‐frequency accommodation cycles and the stratigraphic relationships between coal and clastic sediments. High‐frequency accommodation cycles in the coal are closely related to water table fluctuations in the precursor mires and are driven by high‐frequency climate via changes in the intensity and seasonality of precipitation in a relatively stable subsidence regime. Recognition that the No. 6 coal seam is composed of multiple stacked mires has implications for studies addressing palaeoclimatic inferences and genesis of anomalously thick coals seams.